Attitudes Toward Management Theory as a Factor in Managers’ Relationships With Their Superiors - Miles, Raymond E. (Academy of Management Journal, 1964)
The article presents a study testing the hypothesis that high rated subordinate managers have attitudes toward management concepts and theories more similar to those of their superiors than do their lower rated fellow managers. Twenty-seven groups of managers were selected from production departments in twelve coast electronic firms. The subordinate managers and their immediate superior expressed their attitudes toward various management concepts on the ?What?s Your Theory? questionnaire. The data in the study provide some support for the popular assumption that superiors prefer subordinates with attitudes and views similar to their own.